BVR CCD Photometric observation analysis of spiral galaxy Ic 467 - Ali, Sinan H. (Iraqi Journal of Physics, 2019)
The structure and composition of the stellar population in the surface brightness galaxy Ic 467 is studied using BVR CCD photometry. The observations were obtained on the 1.88m optical telescope of Kottamia Astronomical Observatory, KAO, Egypt. A two-dimensional decomposition of the galaxy bulge and disk components is carried out. A powerful star forming region is observed near the galactic center. Based on the positions of the various components of the galaxy in two color diagrams and the surface brightness of the eastern arms in V filter is brighter than the western arm. From the observations, the surface brightness profiles, Ellipticity profiles, position angle profiles and color indices profiles are described and studied.